Reducing hospital admissions for COPD: perspectives following the Christchurch Earthquake. Issue 1 (2nd August 2018) - Epton, Michael; Limber, Carol; Gullery, Carolyn; McGeoch, Graham; Shand, Brett; Laing, Rose; Brokenshire, Simon; Meads, Andrew; Nicholson-Hitt, Rachel
Abstract : The devastating 2011 earthquake in Christchurch destroyed or badly damaged healthcare infrastructure, including Christchurch Hospital. This forced change in management of exacerbations of chronic obstructive pulmonary disease (COPD), which until that point had frequently led to admission to hospital and focused attention on providing safe community options for care. This paper describes the process of understanding factors contributing to high admission frequency with exacerbations of COPD and also describes a process of change, predominantly to healthcare delivery systems and philosophies, and the subsequent outcomes. What became clear in understanding admissions with COPD to Christchurch Hospital was that the behaviour of the patient, in the context of exacerbations, and the subsequent response of the system to the patient, led to admission being the default option, in spite of low severity of the exacerbation itself. By altering systems' responses to exacerbations, with a linked care process between ambulances, community care and hospitals, we were able to safely reduce admissions for COPD, with a sustained overall reduction in bed-day occupancy for COPD of 48%. We would encourage these discussions and changes to occur without the stimulus of an earthquake in your healthcare environment!